Autopoiesis of the Discourse of Religious Tolerance (Early Intercultural Communication in the 19th Century) - A. Yu. Bendin; N. M. Markova (Концепт: философия, религия, культура, 2021)
The problem of religious tolerance is becoming more and more relevant both for the Russian Federation and the modern world as a whole, since not only the media, but also academic publications almost every day inform us about conflicts between religious communities of local and global scale. The article examines a number of new aspects of the phenomenon of religious tolerance that are revealed when it is described as an autopoiesis of a specific intercultural communicative discourse. This specific discourse is explicitly presented in the texts of the 19th centuries and later texts included in the database of the academic linguistic resource National Corpus of the Russian Language. The texts manifest special forms of implicit tolerance, which is formed, developed and transformed in the global context of intercultural communication, which seeks to distribute the true (“due”, “normative”) and superstitious (“false”, “forbidden”). Starting with the most ancient texts supersticious is intended to mark the difference between permissible (“tolerant”, “ridiculed”) and the unconditionally forbidden (“dangerous”, “intolerant”). The development of communication from the most ancient face-to-face communication to written forms in urban cultures and mass media images of global reality contributes to the formation of an imperial understanding of local features in modern culture. A number of materials from the Russian history of the 19th century show us in detail the development of discourse of tolerance in dialectics with the discourse of intolerance. We can see it from the era of the creation of the Holly Alliance by Alexander I, in which Orthodox Christians, Catholics and Lutherans were proclaimed one Christian people to protective triad of Uvarov and national romanticism, which sought not only to distance itself from everything different, but also to enter into a multifaceted intercultural dialogue. This development placed issues concerning true